Knowledge, attitudes, and practices towards personal data protection in social media among Indonesian college students - Nasrullah, Rulli; Purnamasari, Oktaviana; Patrianti , Tria; Sanjaya, Makroen; Lolombulan Kontu, Study Rizal; Jumroni (Universitas Semarang, 2025)
The issue of personal data protection on the internet has become a significant cause of concern for the Indonesian Government. Millions of people's data on private information has been leaked and traded on marketplace sites. Anticipating the same incident in the future, the Indonesian Government issued Regulation No. 27 of 2022 on Personal Data Protection. However, not all citizens are aware of the regulation. Taking data from 325 students at universities spread across Indonesia using quantitative analysis of knowledge-attitude-practice, this study shows how there is still a lack of understanding among citizens about personal data protection. It shows that citizens are still not worried about publishing their data on social media. Many respondents would still publish personal data on social media accounts and itt can be assumed that many still do not know the importance of protecting personal data and the possibility of misuse of information shared, and also do not understand the importance of protecting personal data uploaded on social media and the possibility of misuse of information.